CHALLENGES BEFORE THE MANAGEMENT OF HUMAN RESOURCES IN THE HEALTH ORGANIZATION - Radeva , Svetlana (EurasianUnionScientists, 2020)
Human resources and their management in an organization is extremely complex, depending on the constantly changing environmental factors, which makes management extremely unpredictable and unsustainable. The organization, such as the hospital, faces a lot of psycho-social characteristics of both the workers in it and the external partners of the organization. The management of the personnel requires a number of activities aimed at attracting, training and development of employees, conducting a flexible policy depending on the requirements of the environment, regulations and continuous technological development. The staff management activities concern: job creation and positions, interviews, drafting of employment contracts and job descriptions, payroll calculation, commissioning, training organization For employees. The monitoring of human resources management demonstrates the need to delegate a number of activities both at the operational level and at the leadership level, to activities requiring swift and responsible decision-making in the health Organisation. The speed of decisionmaking requires the coordination of different levels, leading to the knowledge, skills and ability to predict the outcome, as often in medical care the results are indicative over time. Often in the healing structures requires teamwork, to take complex decisions, on which human lives depend. This requires the assumption of a number of responsibilities, organisational skills and knowledge in carrying out specific activities. Regardless of the different competencies of the staff it is necessary to develop their skills, to conduct continuous training, to build empathy with the hospital organization.